Adscita (Tarmannita) antoniovivesi Efetov & Tarmann, a new species of the genus Adscita Retzius, 1783, from Spain (Lepidoptera: Zygaenidae, Procridinae) - Konstantin A. Efetov; Gerhard M. Tarmann (SHILAP, 2024)
A new species of the genus Adscita Retzius, 1783, viz. Adscita (Tarmannita) antoniovivesi Efetov & Tarmann, sp. nov., was discovered in and is described from Spain. Information on biology and early stages is provided. The new species is named in honour of the Spanish lepidopterologist Dr Antonio Vives.